Case Report: Clinical Features of Childhood Leukoencephalopathy With Cerebral Calcifications and Cysts Due to SNORD118 Variants - Jin, Hong; Ren, Xiaotun; Wu, Husheng; Hou, Yanqi; Fang, Fang (Frontiers in Neurology, 2021)
Background: Leukoencephalopathy with cerebral calcifications and cysts (LCC) is a rare autosomal recessive cerebral microangiopathy. Recently, biallelic variants in a non-protein-coding gene SNORD118 have been discovered to cause LCC. Case Presentation: We here report a genetically confirmed childhood case of LCC. The patient was a 4-year-and-1-month-old boy with focal seizures. The age at onset of his seizure was 10 days after birth. The seizures were well-controlled by antiepileptic treatment but reoccurred twice due to a head impact accident and a fever, respectively. He suffered from a self-limited esotropia and unsteady running gait during the seizure onset. He had the typical neuroimaging triad of multifocal intracranial calcifications, cysts, and leukoencephalopathy. Genetic analysis indicated that he carried compound heterozygous variants of n.*9C>T and n.3C>T in SNORD118, which were inherited from his parents. Conclusion: We report a childhood LCC case with compound heterozygous variants in SNORD118. To the best of our knowledge, the patient reported in our case had the youngest onset age of LCC with a determined genotype. The triad cerebral-imaging findings of calcifications, cysts, and leukoencephalopathy provide a crucial diagnostic basis. Moreover, the gene assessment, together with the clinical investigations, should be considered for the diagnosis of LCC.